2008
DOI: 10.1016/j.nbd.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Adult neurogenesis is functionally associated with AD-like neurodegeneration

Abstract: Alzheimer's disease (AD) is predominantly characterized by progressive neuronal loss in the brain. It has been recently found that adult neurogenesis in the hippocampal dentate gyrus of AD patients is significantly enhanced, while its functional significance is still unknown. By using an AD-like neurodegeneration mouse model, we show here that neurogenesis in the dentate gyrus was neurodegenerative stage-dependent. At early stages of neurodegeneration, neurogenesis was significantly enhanced and newly generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 55 publications
(75 reference statements)
3
59
0
3
Order By: Relevance
“…month-old TgCRND8 compared to non-Tg mice. This increase in BrdU-positive cells may represent an initial compensatory mechanism to enhance cell proliferation in response to A␤PP/A␤ exposure, as proposed by Chen and colleagues [46] and previously observed in TgCNRD8 mice at early stages of the disease [47]. Our results indicate that this initial increase in proliferation does not promote neurogenesis, as no corresponding increase in DCX or BrdU/NeuN-positive cells is observed, possibly because of the toxic environment composed of A␤ [7,8,39].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…month-old TgCRND8 compared to non-Tg mice. This increase in BrdU-positive cells may represent an initial compensatory mechanism to enhance cell proliferation in response to A␤PP/A␤ exposure, as proposed by Chen and colleagues [46] and previously observed in TgCNRD8 mice at early stages of the disease [47]. Our results indicate that this initial increase in proliferation does not promote neurogenesis, as no corresponding increase in DCX or BrdU/NeuN-positive cells is observed, possibly because of the toxic environment composed of A␤ [7,8,39].…”
Section: Discussionsupporting
confidence: 78%
“…Other studies report diminished number of newborn neurons reaching maturation [6,7,[42][43][44][45], partly due to impaired survival of newly generated neurons [44]. Chen et al [46] reported increased neurogenesis at early stages of neurodegeneration but not at late stages, suggesting that dynamic changes in neurogenesis were correlated with the severity of neuronal loss in DG, and perhaps serve as compensatory mechanism following neurodegeneration.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a similar increase in adult hippocampal cell proliferation (measured by multiple endogenous newborn neuron markers) was found in the subgranular zone of human subjects with AD (88). It has therefore been suggested that this increase may be a compensatory repair mechanism (88,90).…”
Section: Discussionmentioning
confidence: 65%
“…Neurodegenerative and pathological processes promote neurogenesis as described for human Alzheimer's and Huntington's disease patients. 18,19 Previous papers found an increase in the number of neural progenitor cells (NPC) following chronic disease of the spinal cord (either for a long time interval following a spinal trauma or during the course of ALS). 20,21 Nonetheless, none of the studies provide evidence for a net increase in neuron number and the prevalent literature suggests that these NPC tend to differentiate into glial cells.…”
Section: Lithium Astrocytes and Neural Progenitor Cellsmentioning
confidence: 99%